Invasive procedures in pre natal diagnosis - Guzmán, Luis (2015)
Oocyte in vitro maturation (IVM) is a reproductive technique that generates oocytes capable of supporting preimplantation embryo development and its complete development, which has been used for a long time in animals but in humans is still an emerging technology. In the last decade, studies have been conducted in order to improve the efficacy of that technology; results obtained by using commercially available media are still inferior to reproductive techniques as in vitro fertilization (IVF). However, collection of mature oocytes in gonadotropins’ hyperstimulated cycles increases the risk of ovarian hyperstimulation syndrome (OHSS) and none of the strategies used to predict its occurrence has completely eliminated the risk. For that reason, implementation of IVM procedures shows interesting perspectives in patients with polycystic ovary (PCO) and polycystic ovary syndrome (PCOS), cancer diagnosis and oocyte maturation failure. Therefore, research is needed in order to optimize this technology which could become a routine technique in assisted reproduction laboratories.